Determinants of Lactic Acidosis in Acute Cyanide Poisonings. Issue 6 (June 2018) - Baud, Frédéric J.; Haidar, Mohamad K.; Jouffroy, Romain; Raphalen, Jean-Herlé; Lamhaut, Lionel; Carli, Pierre
Abstract : Objectives: To investigate the magnitude of lactic acidosis in response to cyanide poisoning compared with the secondary response caused by cardiovascular shock. Design: Retrospective case-control observational study. Setting: University Hospital of Assistance Publique – Hôpitaux de Paris. Subjects: Patients admitted for suspicion of cyanide poisoning or drug overdose. Medical charts provided by Assistance Publique - Hôpitaux de Paris of patients between January 1988 and December 2015. Intervention: None. Measurements and Main Results: Twelve cyanide poisoned patients were matched to 48 controls by age, sex, systolic blood pressure, catecholamine administration, and outcome at discharge from ICU. Extracted data included age, sex, vital signs, symptoms, biochemical parameters, toxicological analysis, treatment, and outcome. Non-parametric tests were used. Multivariable analysis was used to adjust for confounders causing hyperlactacidemia. The median blood lactate concentration was significantly greater in the cyanide group (15.6 mmol/L) compared to the control group (4.1 mmol/L; p = 0.0003). Similarly, blood lactate concentration greater than or equal to 8 mmol/l was observed in 83% of the cyanide cases versus 27% of the matched controls. Multivariate analysis conferred hyperlactacidemia as the lone factor which significantly predicted cyanide poisoning at an odds of 73.0 (5.7-936.1). Moreover, blood cyanide level significantly correlated with the increase of blood lactate ( p = 0.0033). Conclusions: This study supports the hypothesis lactic acidosis primarily results from the direct toxicity of cyanide.